Peranan Tugas Sekretaris pada Balai Penyuluhan Pertanian dan Kehutanan Peereulak Aceh Timur - Aisyah; M Djamil HS (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2021)
This research investigates the role of secretaries in various organizational contexts, with a focus on smooth administration, emotional intelligence, use of technology, and strategic role in decision making. Qualitative research methods were used by conducting interviews, case studies and document analysis of various organizations and institutions. The findings show that the secretary's role is not only limited to ordinary administrative tasks, but also includes managerial, interpersonal, and strategic aspects that are important in supporting the operational effectiveness and efficiency of the organization. Emotional intelligence has also been found to play an important role in secretarial performance, while the use of technology has influenced the way secretaries manage information and support decision making. Managerial implications of this research include the need to recognize and develop the role of secretaries as strategic partners in organizations, while future research can expand the scope of samples and research methods to gain a more holistic understanding of the role of secretaries in various organizational.